Nanostructured Silicon‐Based Heterojunction Solar Cells with Double Hole‐Transporting Layers. (3rd December 2018) - Shen, Suling; Zhang, Jie; Zhou, Shuang; Han, Yujie; Gao, Peng; Sun, Baoqun; Zhao, Ni; Wong, Ching‐Ping
Abstract: Hybrid nanostructured silicon–organic solar cells have been pursued as a low‐cost solution for silicon photovoltaic devices. However, it is difficult for the organic semiconductor, typically poly(3, 4‐ethylenedioxythiophene):polystyrene (PEDOT:PSS), to fully cover the nanostructured silicon surface due to the high surface tension of the polymer solution and the small size of the cavities in nanostructured silicon. As a result, the performance of the hybrid solar cells is limited by the defect‐induced surface recombination and poor hole extraction. In this work, an inorganic hole‐transporting layer, copper(I) thiocyanate (CuSCN), is introduced between silicon nanowire (SiNW) and PEDOT:PSS to improve the junction quality. The effect of CuSCN on as‐fabricated SiNW and tetramethylammonium hydroxide (TMAH)‐treated SiNW structures is examined, and it is shown that in both cases CuSCN can well cover the SiNW surface due to the easy penetration of its solution into the silicon nanostructure. As a result, the power conversion efficiency of the solar cells has been dramatically improved from 7.68% to 10.5% for as‐fabricated SiNW‐based‐hybrid cells, and from 10.75% to 12.24% for TMAH‐passivated SiNW‐based‐hybrid cells, suggesting that the double hole‐transporting layer approach can effectively improve the junction quality in hybrid organic‐nanostructured silicon‐based devices. Abstract : An inorganic hole‐transporting layer, copper(I) thiocyanate (CuSCN), is introduced between silicon nanowire (SiNW) and poly(3, 4‐ethylenedioxythiophene):polystyrene (PEDOT:PSS) to improve the junction quality. The power conversion efficiency of the solar cells has been dramatically improved 10.75–12.24%, suggesting that the double hole‐transporting layer approach can effectively improve the junction quality in hybrid organic‐nanostructured silicon based devices.